Signaling Adaptor Protein SH2B1 Enhances Neurite Outgrowth and Accelerates the Maturation of Human Induced Neurons. (15th April 2014) - Hsu, Yi-Chao; Chen, Su-Liang; Wang, Ya-Jean; Chen, Yun-Hsiang; Wang, Dan-Yen; Chen, Linyi; Chen, Chia-Hsiang; Chen, Hwei-Hsien; Chiu, Ing-Ming
Abstract : The authors show that SH2B adaptor protein 1β can enhance neurite outgrowth of induced neurons reprogrammed from human fibroblasts as early as day 14, when combined with miR124 and transcription factors BRN2 and MYT1L under defined conditions. These enhanced induced neurons showed canonical neuronal morphology and expressed multiple neuronal markers and functional proteins for neurotransmitter release. Abstract: : Recent advances in somatic cell reprogramming have highlighted the plasticity of the somatic epigenome, particularly through demonstrations of direct lineage reprogramming of adult mouse and human fibroblasts to induced pluripotent stem cells (iPSCs) and induced neurons (iNs) under defined conditions. However, human cells appear to be less plastic and have a higher epigenetic hurdle for reprogramming to both iPSCs and iNs. Here, we show that SH2B adaptor protein 1β (SH2B1) can enhance neurite outgrowth of iNs reprogrammed from human fibroblasts as early as day 14, when combined with miR124 and transcription factors BRN2 and MYT1L (IBM) under defined conditions. These SH2B1-enhanced iNs ( S -IBM) showed canonical neuronal morphology, and expressed multiple neuronal markers, such as TuJ1, NeuN, and synapsin, and functional proteins for neurotransmitter release, such as GABA, vGluT2, and tyrosine hydroxylase. Importantly, SH2B1 accelerated mature process of functional neurons and exhibited action potentials as early as day 14; without SH2B1, the IBM iNs do not exhibit action potentials until day 21. Our data demonstrate that SH2B1 can enhance neurite outgrowth and accelerate the maturation of human iNs under defined conditions. This approach will facilitate the application of iNs in regenerative medicine and in vitro disease modeling.